(untitled) (Tanzania Medical Journal, 2017)
BackgroundHypertension is a known risk factor for the development of renal dysfunction. With the increasing burden of hypertension in developing countries, especially due to lifestyle modifications, we expect a rise in the development of renal dysfunction. The prevalence, pattern and predictors of renal dysfunction among hypertensive patients in sub-Saharan Africa have not been well described.MethodsAn analytical cross-sectional study was conducted at Bugando Medical Centre (BMC) outpatient clinic from February 2013 to April 2013. The primary end point was renal dysfunction defined as an estimated glomerular filtration rate (eGFR) < 90ml/min/1.73m2 (calculated using the Cockroft-Gault equation) and/or the presence of albuminuria.ResultsThe population consisted of more females than males (54.7% vs. 45.3%). The majority of the population came from urban areas. The prevalence of renal dysfunction was found to be 53.9%. Older age, female gender, obesity, high systolic blood pressure and type of antihypertensive medications were found to be strong predictors of renal dysfunction.ConclusionRenal dysfunction was highly prevalent in this population of non-diabetic hypertensive outpatients in North-western Tanzania. This highlights the critical and underappreciated need to monitor renal function in hypertensive patients in sub-Saharan Africa given the increasing high burden of hypertension in the region.